EXPERIMENTAL AND NUMERICAL STUDY OF TUNNEL VARIATIONS EFFECTS ON BLAST WAVE TRANSMISSION MECHANISM - Hung, Cheng-Wei; Pi , Sheng-Jung; Chen, Pen-Chou (Journal of Applied Engineering Science, 2026)
This study investigates the effects of tunnel configuration changes on blast pressure transmission under near-field explosion conditions using both experimental and numerical approaches. Small-scale models were employed to conduct explosion tests, including near-surface detonations and variations in tunnel patterns. Numerical simulations utilizing ALE (Arbitrary Lagrangian-Eulerian) fluid-structure interaction were performed to evaluate blast pressure transmission. The analysis revealed that elbow-type, T-type, and branched tunnels exhibited varying effects on blast pressure transmission, with significant differences in pressure between the inner and outer walls of the tunnels’ bend sections. In elbow-type tunnels, the inner wall experienced greater blast pressure than the outer wall, whereas the opposite was observed in T-type and branched tunnels. The findings demonstrate that the numerical model accurately reflects experimental blast pressure transmission patterns.